How to know a person eaudiobook The art of seeing others deeply and being deeply seen. - Brooks, David (Books on Tape, 2023)
NEW YORK TIMES BESTSELLER • A practical, heartfelt guide to the art of truly knowing another person in order to foster deeper connections at home, at work, and throughout our lives—from the author of The Road to Character and The Second Mountain “More than a guide to better conversations, it’s a blueprint for a more connected and humane way of living. It’s a must-read for anyone looking to deepen their relationships and broaden their perspectives.”—Bill Gates, GatesNotes (Summer Reading Pick) As David Brooks observes, “There is one skill that lies at the heart of any healthy person, family, school, community organization, or society: the ability to see someone else deeply and make them feel seen—to accurately know another person, to let them feel valued, heard, and understood.” And yet we humans don’t do this well. All around us are people who feel invisible, unseen, misunderstood. In How to Know a Person, Brooks sets out to help us do better, posing questions that are essential for all of us: If you want to know a person, what kind of attention should you cast on them? What kind of conversations should you have? What parts of a person’s story should you pay attention to? Driven by his trademark sense of curiosity and his determination to grow as a person, Brooks draws from the fields of psychology and neuroscience and from the worlds of theater, philosophy, history, and education to present a welcoming, hopeful, integrated approach to human connection. How to Know a Person helps readers become more understanding and considerate toward others, and to find the joy that comes from being seen. Along the way it offers a possible remedy for a society that is riven by fragmentation, hostility, and misperception. The act of seeing another person, Brooks argues, is profoundly creative: How can we look somebody in the eye and see something large in them, and in turn, see something larger in ourselves? How to Know a Person is for anyone searching for connection, and yearning to be understood.